Legal Analysis of the Rights and Obligations of Heirs in Full Inheritance Based on the Civil Code - Sarles Gultom; Parlin Dony Sipayung; Van Lodewijk Purba; Novi Marnata Roma Ulinta; Bela Riksa Z Damanik (Program Pascasarjana UIN Sumatera Utara, 2023)
Inheritance is a regular process in civil law that regulates a person's assets after death to his/her heirs. According to Article 832 of the Civil Code, those who are entitled to be heirs are blood relatives, both those who are legitimate according to the law and those who are not married, and the longest-living husband and wife. This study aims to explain the rights and obligations of heirs in inheritance. The problem is formulated into three questions which in essence will discuss the regulation of the rights and obligations of heirs in inheritance entirely based on the civil code, as well as the role of heirs in the inheritance process. The research method used is the Normative Juridical legal research method. Data were collected through literature searches or libraries. Data analysis was carried out qualitatively, so that answers presented in the formulation of the problem could be found. The results of the study found that the Civil Code affirms specific rights and obligations for heirs. The rights of heirs according to the Civil Code include the right to receive a portion of the inheritance, including legally valid assets. They also have the right to file a lawsuit to protect their inheritance rights. On the other hand, heirs have an obligation to respect the will stated in the will, if any, and to divide the inheritance fairly in accordance with the provisions stipulated in the Civil Code. This obligation includes proportional distribution between heirs and settlement of debts and other obligations on the inheritance. Thus, the Civil Code provides a clear and firm legal framework for heirs in fully managing inheritance. To provide a deep understanding of the rights and obligations of heirs in inheritance, the application of civil law can be carried out fairly and in accordance with applicable provisions.